Role of elevated plasma soluble ICAM-1 and bronchial lavage fluid IL-8 levels as markers of chronic lung disease in premature infants. Issue 10 (October 1995) - Little, S; Dean, T; Bevin, S; Hall, M; Ashton, M; Church, M; Warner, J; Shute, J
Abstract : BACKGROUND--Pulmonary neutrophilia characterises both the relatively transient inflammation associated with infant respiratory distress syndrome (IRDS) and the persistent inflammation of chronic lung disease. The possibility that persistently raised markers of inflammation indicate the development of chronic lung disease in low birth weight (< 1730 g) preterm (< 31 weeks) infants was therefore investigated. METHODS--Soluble ICAM-1 (sICAM-1) levels in plasma, and interleukin (IL)-8 and myeloperoxidase (MPO) levels in bronchial lavage fluid (BLF) obtained from 17 infants on days 1, 5, and 14 following birth were measured and correlations with the number of neutrophils in BLF sought. Peripheral neutrophils were isolated on Polymorphoprep and chemotactic responsiveness to IL-8 was assessed using micro Boyden chambers. RESULTS--Sixteen infants developed IRDS and, of these, 10 infants subsequently developed chronic lung disease. Levels of IL-8 in BLF at 14 days of age correlated with the long term requirement for intermittent positive pressure ventilation (IPPV). Interleukin 8 levels in BLF correlated with neutrophil numbers and MPO concentration, suggesting both recruitment and activation in response to this cytokine. Antibody depletion studies showed that approximately 50% of total neutrophil chemotactic activity in BLF was due to IL-8. No difference in peripheral neutrophil chemotactic responsiveness at any age was observed for infants with IRDS or chronic lung disease. Plasma soluble intercellular adhesion molecule (sICAM-1) was higher at 14 days of age in infants who developed chronic lung disease than in those with resolving IRDS, and correlated with severity of disease, as indicated by duration of IPPV. CONCLUSIONS--The results indicate that high levels of plasma sICAM-1 and IL-8 in BLF at day 14 correlate with the development of chronic lung disease and indicate the severity of disease.